Development of a sustainable route for the production of high‐fructose syrup from the polyfructan inulin - Kongkona Saikia; Hridya Radhakrishnan; Abiram Karanam Rathankumar; Siva Gokul Senthil Kumar; Shravani Kalita; Jenet George; Sivanesan Subramanian; Vaidyanathan Vinoth Kumar (IET Nanobiotechnology)
Abstract The authors used mesoporous silica microspheres as a support for the immobilization of inulinase from Aspergillus brasiliensis MTCC 1344 by the process of cross‐linking. Under optimized operating conditions of pH 6.0, particle/enzyme ratio of 2.0:1.0 and glutaraldehyde concentration of 7 mM, a maximum immobilization yield of 90.7% was obtained after a cross‐linking time of 12.25 h. Subsequently, the cross‐linked inulinase was utilized for the hydrolysis of 5% inulin, and a maximum fructose concentration of 31.7 g/L was achieved under the optimum conditions of pH 6.0 and temperature 60°C in 3 h. Furthermore, on performing reusability studies during inulin hydrolysis, it was observed that the immobilized inulinase could be reused up to 10 subsequent cycles of hydrolysis, thus providing a facile and commercially attractive process of high‐fructose syrup production.